Study of the Stimulating and Attractive Factors of Oviposition of Culex pipiens (Diptera; Culicidae) in Different Environments - Saliha, Benhissen; Zakaria, Hedjouli; Yagoub, Asloum Abdelmadjid; Fatiha, Masna; Siham, Bounadji; Wafa, Habbachi (Iraqi Journal of Science, 2023)
The study of the chemical and physical factors that induce egg-laying is important for understanding mosquitoes' ecology. These substances may also help assess and control mosquito populations. With this in mind, we have highlighted the attractiveness of Culex pipiens gravid females concerning the containers' color and surface, which has enabled us to show that females of this species are always attracted to large containers of yellow. The ethological tests were made with four biopesticides on the attractiveness of C. pipiens females. It has been observed that the highest densities of the eggs are deposited in the container which contains the biopesticides extracts compared to that which includes the spring water with a significant difference between the two environments (p: 1.00). This choice is due to the presence of odorous molecules which attract the mosquito.